Estimating the Effects of Dental Caries and Its Restorative Treatment on Periodontal Inflammatory and Oxidative Status: A Short Controlled Longitudinal Study - Kanjevac, Tatjana; Taso, Ervin; Stefanovic, Vladimir; Petkovic-Curcin, Aleksandra; Supic, Gordana; Markovic, Dejan; Djukic, Mirjana; Djuran, Boris; Vojvodic, Danilo; Sculean, Anton; Rakic, Mia (Frontiers in Immunology, 2021)
Dental caries and periodontitis are among the most common health conditions that are currently recognized as growing socio-economic problems relating to their increasing prevalence, negative socio-economic impact, and harmful effects on systemic health. So far, the exact effects of caries and standard restorative materials on periodontal inflammatory and oxidative status are not established. The present study aimed to investigate the effect of caries and its restoration using standard temporary and permanent filling materials on a panel of 16 inflammatory and oxidative markers in gingival crevicular fluid (GCF) of periodontally healthy individuals, 7 (D7) and 30 (D30) days post-restoration, while the intact teeth represented the control. One hundred ninety systemically and periodontally healthy patients with occlusal caries underwent standard cavity preparation and restorations with one of six standard temporary or permanent restorative material according to indication and randomization scheme. Interleukin (IL)-2, IFN- γ, IL-12, IL-17A, IL-13, IL-9, IL-10, IL-6, IL-5, IL-4, IL-22, TNF-α, IL1- β, thiobarbituric acid reactive substances, superoxide dismutase, and reduced form of glutathione were measured in GCF samples by flowcytometry and spectrophotometry in aid of commercial diagnostic assays. Caries affected teeth exhibited significantly increased IL-1 β, IL-17, IL-22, and TBARS and decreased IL-9 concentrations compared to healthy controls. Treatment generally resulted in an increased antioxidant capacity with exception of zinc-polycarboxylate cement showing distinctive inflammatory pattern. Comparison of inflammatory and oxidative profiles in temporary and permanent restorations showed material-specific patterning which was particularly expressed in temporary materials plausibly related to greater caries extension. Caries affected teeth exhibited a balanced inflammatory pattern in GCF, with a general tendency of homeostatic re-establishment following treatment. Restorative materials did not provide specific pathological effects, although some material groups did exhibit significantly elevated levels of inflammatory and oxidative markers compared to healthy controls, while the material-specific patterning was observed as well.